Analysis of usage of genetic and tabu search algorithms in shop scheduling - Šakurovas , Edgaras; Listopadskis, Narimantas (Lietuvos matematikos rinkinys, 2008)
A wide area of scheduling problem is industrial so-called shop scheduling (Job Shop, Flow Shop and Open Shop) which has important applications in real world industrial problems. Metaheuristic algorithms (Genetic and Tabu search algorithms in this case) seem to be one of the best candidates for finding nearbyoptima in proper time. In this work we implemented several genetic algorithms (separated by values of their parameters) and several Tabu search algorithms (separated by neighborhood of solution). Finally, implemented eight algorithms are examined for random shop scheduling problems in terms of various criteria.